Details of a water target used in a high-current application for aneutrino-physics experiment and the direct measurement of the incidentproton beam by the induced change in the water conductivity - 348495 Dombeck, T.; Finch, A.; Grisham, D. L.
A water target was constructed for use in a low-energy neutrino physicsexperiment at the Los Alamos Meson Physics Facility. For 800 MeV incidentprotons, a water target may be close to optimal in the production ofpositive that subsequently decay in flight, yielding muon neutrinos,especially if used in conjuction with a pion- focusing device. We discussthe special features of the stress caused by the large proton currentsused in experiment. Our target also included internal monitors to measurechanges in intensity of protons inside the target and gave a measure ofthe beam alignment.